Role of Restorative Justice in Strengthening Social Ties and Reducing E- Crime using Social Bond Theory (SBT) and Re-integrative Shaming Theory (RST) - Shari, Munahi Bin Khanthl Bin (Journal of Ecohumanism, 2025)
Restorative justice has emerged as a powerful framework within the criminal justice system, offering innovative solutions to strengthen the social relations among individuals and decrease e-crimes. This study aims to explore the impact of restorative justice on building trust between individuals in society and how restorative justice contributes to strengthening social ties. Moreover, the study intends to analyze the psychological and social effects of restorative justice on victims and perpetrators. The study adopted an analytical and descriptive design. The researcher first of all analyzed the previous studies on restorative justice and crime reduction. This helped reach at a deep dimension of the current study topic. Additionally, case studies were revised and examined to enrich the study with examples of successful restorative justice programs. Given the complexity and variety of crime, as well as the limitations of punishment-focused court systems, studying the role of restorative justice in reducing crime and strengthening social ties presents a significant challenge. Despite advancements in understanding the drivers of criminal behavior, many traditional legal systems fail to address the root causes of crime or help offenders change, relying instead on punishment as a deterrent. Most of these groups, ranging from the police to the politicians and locals, also lack what they need to implement the restorative methods that remain. This general lack of knowledge and experience is leading to opportunities being missed in using restorative approaches to lower crime and build better communities. In fact, if restorative justice systems are to succeed and realize their goals, this will be made possible only through major initiatives of education and the acceptance of these frameworks. Cultural differences and varied views on justice can slow down the adoption of restorative methods.